The quality of life of mothers who have children with developmental disorders - Malan, Antonetta (My University, 2020)
Limited research has been performed to establish how having a child with a developmental disorder affects the quality of life (QOL) of mothers in South Africa. Developmental disorders encompass developmental delay (DD) and intellectual disability (ID) and refer to significant limitations in different facets of development. They occur during childhood and often persist into adulthood and have a severe impact on psychological and social well-being. Quality of life is a universal concept that refers to an individual’s sense of overall well-being. Having a child with a developmental disorder can have an impact on the QOL of mothers caring for them. Limited research has been performed to establish how having a child with a developmental disorder affects the quality of life (QOL) of mothers in South Africa. The aim of this study was to establish whether having a child with a developmental disorder significantly influences the QOL of South African mothers. This was a descriptive case-control study that used quantitative research methods. It was nested within two larger studies: Deciphering Developmental Delay (DDD) in Africa and the Long-term Effects of Gestational Diabetes. The World Health Organization Quality of Life Abbreviated Version (WHOQOL-BREF) questionnaire was used as a researcher administered tool to assess the QOL of 20 mothers of children with developmental disorders (cases) and 20 mothers of typically developing children (controls). The tool consists of 26 questions and assesses QOL in four domains: physical, psychological, social and environmental. The QOL measures in the cases were statistically significantly lower than those for the controls in the physical (p=0.01), psychological (p=0.004) and environmental (p<0.001) domains. The QOL measure in the social domain showed no significant difference between cases and controls (p=0.077). No demographic and socio-economic factors were associated with low or high QOL in any one of the four domains, and no significant differences were in demographics or socio-economic status seen between cases and controls. This study has shown that having a child with a developmental disorder significantly lowers the QOL of mothers in South Africa. Healthcare providers need to be aware of this. Interventions are needed, such as referral for further assistance, including support groups and psychological care.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Medicine (Genetic Counselling), 2020